Frequency and antimicrobial susceptibility of bacteria causing mastitis in a dairy farm in Trujillo, Peru - Rodríguez Pérez, Roxana (2017)
The frequency and antimicrobial susceptibility of mastitis caused by bacteria in cattle from a dairy farm in the Conache district, Trujillo, Peru, between September and December 2015 were determined. Milk samples were collected from 140 quarters of 35 cows that were checked for mastitis by direct observation in a cup with black background. For the microbiological analysis, the samples were cultured in blood agar and MacConkey agar and incubated at 37 °C for 24 h. To determine gram-positive bacteria tests of catalase, coagulase, mannitol fermentation and hemolysis were performed, and for gram-negative triple sugar iron agar (TSI), lysine-iron agar (LIA), Simmons citrate, urease, indole, methyl red, Voges Proskauer and glutamate broth were used. Antimicrobial susceptibility was determined by the Kirby-Bauer method with ampicillin, clindamycin, doxycycline, erythromycin, streptomycin, gentamicin, oxacillin and rifampicin disks. Thirty one cows with bacterial mastitis were detected, where 76% had gram-negative bacteria and 24% had gram-positive bacteria. The most frequent gram-negative bacteria were E. coli (28%) and Klebsiella sp. (24%), and the most frequent gram-positive bacteria was Staphylococcus aureus (16%). Pseudomonas aeruginosa was resistant to most antibiotics except erythromycin (intermediate susceptibility). E. coli presented intermediate susceptibility to erythromycin and resistance to oxacillin and rifampicin. Staphylococcus aureus presented intermediate susceptibility to clindamycin and erythromycin and resistance to ampicillin.